2019
DOI: 10.1073/pnas.1902889116
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering of a ubiquitin-variant inhibitor of APC/C identifies a cryptic K48 ubiquitin chain binding site

Abstract: Ubiquitin (Ub)-mediated proteolysis is a fundamental mechanism used by eukaryotic cells to maintain homeostasis and protein quality, and to control timing in biological processes. Two essential aspects of Ub regulation are conjugation through E1-E2-E3 enzymatic cascades and recognition by Ub-binding domains. An emerging theme in the Ub field is that these 2 properties are often amalgamated in conjugation enzymes. In addition to covalent thioester linkage to Ub’s C terminus for Ub transfer reactions, conjugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 56 publications
(104 reference statements)
1
30
0
Order By: Relevance
“…A crystal structure of UbV W revealed a domain-swapped dimer with an extended β1 strand that forms an antiparallel β-sheet with the opposite subunit (6). Watson et al (6) note that such swapped dimeric structures have been observed in other UbVs (14,15) and collectively display flexibility across the dimer interface. In UbV W , Gly10 is replaced with tryptophan and situated at the center of the extended β1 strand (6).…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…A crystal structure of UbV W revealed a domain-swapped dimer with an extended β1 strand that forms an antiparallel β-sheet with the opposite subunit (6). Watson et al (6) note that such swapped dimeric structures have been observed in other UbVs (14,15) and collectively display flexibility across the dimer interface. In UbV W , Gly10 is replaced with tryptophan and situated at the center of the extended β1 strand (6).…”
mentioning
confidence: 89%
“…Identifying receptor sites for ubiquitin de novo is challenging, as ubiquitin-binding domains are diverse in structure and binding mechanism, resulting in no globally shared consensus sequence (5). In PNAS, Watson et al (6) present a workflow that can be applied broadly to discover new ubiquitin-binding sites. They apply this method to the 1.2-MDa E3 ligase anaphase-promoting complex/cyclosome (APC/C), which promotes ubiquitindependent turnover of cell cycle regulators, including cyclins, to control cell division.…”
mentioning
confidence: 99%
See 3 more Smart Citations